Representation of Cultural Awareness in EFL Textbooks in Indonesian Secondary Schools: A Descriptive Qualitative Study - Sholihah, Mar’atus (Fast in Humanities, 2026)
This study aims to examine how cultural awareness is represented in Indonesian secondary school EFL textbooks. Cultural awareness forms essential component of intercultural communicative competence, and textbooks serve as primary sources shaping learners’ exposure to cultural perspectives. Depth and orientation of such representation require systematic investigation. The study employs descriptive qualitative design using qualitative content analysis. Corpus consists of three nationally aligned secondary school EFL textbooks at grade seven, eight, and nine levels. Unit of analysis includes reading texts, dialogues, visual images, and learning activities. Cultural awareness is analyzed through five categories: self-cultural awareness, awareness of other cultures, critical cultural reflection, cultural values and norms, and representational bias. Data are coded and examined to identify forms and structural patterns of representation. Findings show that cultural awareness is constructed mainly through descriptive presentation of local identity and selective exposure to foreign contexts. Narrative texts and visuals emphasize shared practices and socially endorsed norms. Foreign cultures appear predominantly through English speaking references with limited regional diversity. Reflective tasks are present but remain peripheral and largely restricted to surface comparison. Cultural awareness functions primarily as structured knowledge embedded in language themes rather than as sustained intercultural inquiry. Representational framing and pedagogical sequencing shape depth of engagement. Inclusion of cultural content alone does not ensure critical intercultural development.